Insights into the Oxidant/Polymer Interfacial Growth of Vapor Phase Polymerized PEDOT Thin Films. Issue 18 (25th June 2018) - Sharma, Anirudh; Andersson, Gunther; Rivnay, Jonathan; Alvino, Jason F.; Metha, Gregory F.; Andersson, Mats R.; Zuber, Kamil; Fabretto, Manrico
Abstract: The vapor phase polymerization (VPP) technique is used to produce thin films of poly(3, 4‐ethylenedioxythiopene) (PEDOT) in which the Fe(III)Tosylate oxidant is altered. The oxidant is changed with the addition of an amphiphilic co‐polymer having different molecular weights, namely 2800 Da. and 5800 Da. Resulting PEDOT films produce conductivities of ≈1500 and ≈3000 S cm −1 respectively. Small angle X‐ray diffraction (SA‐XRD) indicates that the oxidant incorporating the larger molecular weight co‐polymer possesses ordered structure and that this in turn helps "template" the PEDOT during film formation. The structure and composition of the bottom (i.e. initial film formation) and top (i.e. final film formation) PEDOT surfaces are studied using surface sensitive analytical techniques; small angle X‐ray diffraction (SA‐XRD), ultraviolet photoelectron spectroscopy (UPS), 2D grazing incidence X‐ray diffraction (2D‐GIXD), metastable induced electron spectroscopy (MIES) and neutral impact collision ion scattering spectroscopy (NICISS). The results indicate that the increase in conductivity using the larger molecular weight co‐polymer additive is due to the film having larger lamella‐ and π‐stacking regions in addition to doping levels which remain unchanged throughout film formation. These conclusions are further supported by results obtained on a model PEDOT:Tosylate system using density functional theory (DFT) calculations. Abstract : Vapor phase polymerized poly(3, 4‐ethylenedioxythiopene) (PEDOT) using two oxidants is studied using small angle X‐ray diffraction (SA‐XRD), UV photospectroscopy (UPS), 2D grazing incidence X‐ray diffraction (2D‐GIXD), metastable induced electron spectroscopy (MIES), and neutral impact collision ion scattering spectroscopy (NICISS) to examine polymer growth and conductivity. Order present in one oxidant results in PEDOT with larger grains and consistent doping throughout.